OP0006 Long-Term Safety and Effectiveness of Adalimumab in Children with Moderately to Severely Active Polyarticular or Polyarticular-Course Juvenile Idiopathic Arthritis. (10th June 2014) - Horneff, G.; Ruperto, N.; Wallace, C.; Bereswill, M.; Cardoso, A.; Kalabic, J.; Kupper, H.; Brunner, H.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is one of the most common rheumatic diseases of childhood. Adalimumab (ADA) is approved for use in moderate to severe polyarticular JIA (pJIA) patients (pts) ≥4 years (yrs) in the US, EU, Australia, and Japan, and was recently approved in EU for pts 2 to <4 yrs. Objectives: To evaluate long-term safety and effectiveness of ADA in pts with moderately to severely active pJIA who are prescribed and treated with ADA in routine clinical practice. Methods: This is an ongoing, multicenter, non-interventional, observational registry of pts diagnosed with moderately to severely active pJIA that are prescribed and treated in a routine clinical setting with either ADA ± ethotrexate (MTX) or MTX alone. Approximately 800 pts (500 in ADA arm/300 in MTX arm) will be enrolled in the US, EU, and Australia. The follow-up observational period is 10 yrs from enrollment into one of the treatment arms. For pts that switch from MTX monotherapy to ADA ± MTX, the 10 yr follow-up period will begin when they enroll into the ADA arm. Observational adverse events (AEs) were recorded from the first day in the registry through last contact, irrespective of treatment duration. Clinical outcomes were assessed by 71-joint juvenile arthritis disease activity score (JADAS71). Results: As of June 2013, 765 pts (459 in ADA arm/306 in MTX arm) were enrolled and treated. The mean pJIA disease duration at baseline was 1.3 and 3.8 yrs for MTX and ADA arms, respectively. At baseline, there was a mean AJC of 5.8 and disability index of childhood health assessment questionnaire (DICHAQ) of 0.6 for both groups. Overall, 131 pts (42.8%) in the MTX arm and 81 pts (17.6%) in the ADA arm have discontinued registry drug. Of those, 23 (7.5%) and 25 (5.4%) pts in the MTX and ADA arm, respectively, discontinued due to an AE, and 34 out of the 131 pts in the MTX arm discontinued as they switched to the ADA arm. The observational AEs are summarized in the Table. No deaths, malignancies, or opportunistic infections were reported. 12 (2.6%) pts in the ADA arm had a serious infectious AE (including acute tonsillitis, cellulitis, gastroenteritis, mononucleosis, viral meningitis, pneumonia, pyelonephritis, scarlet fever, subcutaneous abscess, tonsillitis, urinary tract infection, and varicella). Frequencies and rates of treatment-emergent AEs were similar to those reported for observational AEs. Mean JADAS71 improved from 13.1 at baseline to 11.2, 6.4, 5.1 at months 1, 3 and 6 for pts in the MTX arm and from 12.1 at baseline to 8.5, 5.7, 5.4 in the ADA arm, respectively (observed data). Conclusions: Overall, ADA is well-tolerated in these pts with active pJIA. No new safety signals were observed, and based on this analysis, the known safety profile of ADA remains unchanged. Acknowledgements: AbbVie sponsored the study (NCT00783510 ), contributed to the design, and participated in collection, analysis, and interpretation of data, and in writing, reviewing, and approval of the final version. Medical writing support was provided by Jessica L. Suboticki, PhD, of AbbVie. Disclosure of Interest: G. Horneff Grant/research support: AbbVie, Pfizer, and Roche, Speakers bureau: AbbVie, Novartis, Pfizer, and Roche, N. Ruperto Employee of: GASLINI Hospital, which has received contributions to support the research activities of the network of PRINTO from AbbVie Inc., AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Eli Lilly and Co., "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, and Wyeth Pharmaceuticals, Speakers bureau: Astellas, AstraZeneca, Bristol-Myers Squibb, Italfarmaco, Janssen Biologics B.V., MedImmune, Roche, and Wyeth/Pfizer, C. Wallace Grant/research support: Pfizer and Amgen, Consultant for: Amgen and Novartis, M. Bereswill Shareholder of: AbbVie, Employee of: AbbVie, A. Cardoso Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, H. Brunner Consultant for: AbbVie Inc., AstraZeneca, Centocor, Bristol-Myers Squibb, Pfizer, Regeneron, Hoffman La-Roche, Novartis, UCB, and Genentech, Speakers bureau: Genentech Pharmaceuticals DOI: 10.1136/annrheumdis-2014-eular.1281